1972
DOI: 10.1172/jci106839
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Binding by Human Serum Prealbumin (TBPA). ELECTROPHORETIC STUDIES OF TRIIODOTHYRONINE-TBPA INTERACTION

Abstract: A B S T R A C T Thyroxine-binding prealbumin (TBPA) in normal human serum has been shown in a polyacrylamide gel electrophoresis system to bind 7-9% of tracer level purified ['I]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…TTR is a major serum thyroid hormone binding protein with a molecular mass of 14 kDa [10] which was formerly known as thyroxine-binding prealbumin protein. It was first recognized to bind thyroxine (T4) in 1958 [11] and subsequently shown that TTR also binds to retinol-binding protein and thus plays a role in the transport of vitamin A [12] , [13] .Thus, the name was changed to transthy(roxin)retin(ol) for denoting its dual transport function [14] . Plasma TTR is synthesized by the hepatic parenchymal cells while in fetal life it is synthesized by the yolk sac of endothelium [15] .…”
Section: Introductionmentioning
confidence: 99%
“…TTR is a major serum thyroid hormone binding protein with a molecular mass of 14 kDa [10] which was formerly known as thyroxine-binding prealbumin protein. It was first recognized to bind thyroxine (T4) in 1958 [11] and subsequently shown that TTR also binds to retinol-binding protein and thus plays a role in the transport of vitamin A [12] , [13] .Thus, the name was changed to transthy(roxin)retin(ol) for denoting its dual transport function [14] . Plasma TTR is synthesized by the hepatic parenchymal cells while in fetal life it is synthesized by the yolk sac of endothelium [15] .…”
Section: Introductionmentioning
confidence: 99%
“…[125I]T4 was purchased from Amersham and its purity verified by thin layer chromatography (8). 45Ca was obtained from ICN Radioisotopes (Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…1 Part of a report read at the Sixth International Thyroid Conference, Vienna, June 1970. members without the trait. All 24 subjects were clinically euthyroid and had no history of thyroid disease or drug treatment.…”
Section: Subjectsmentioning
confidence: 99%
“…Three bindingproteins have been identified: thyroxinebinding globulin (TBG), thyroxine-binding pre-albumin (TBPA) and albumin. TBG, being the major transport protein, carries about 55 to 75% of the TT 4 (1,2). In subjects with inherited TBG deficiency, low TT 4 values and high percentages of free thyroxine (FT 4 ) are found in the blood.…”
mentioning
confidence: 99%